Principles of healthcare management for patients with pulmonary hypertension: focus on continuity - V. A. Ryabkov; N. N. Vezikova; N. S. Goncharova; M. A. Simakova; O. M. Moiseeva (Российский кардиологический журнал)
In managing care for patients with rare, rapidly progressive pathologies such as pulmonary hypertension (PH) and chronic thromboembolic hypertension (CTEPH), early diagnosis and speed of routing are of particular importance. Reducing the time spent on patient routing reduces the risk of disease progression, the rate of hospitalizations, and thereby the socioeconomic burden of the disease.In the Republic of Karelia, an algorithm for routing patients with PH and CTEPH has been created, which is an example of a successful healthcare management.